CBMS-1 TARGETING GLUTAMINE METABOLISM IN IDH-MUTANT GLIOMAS. (3rd December 2022) - Ohba, Shigeo; Teranishi, Takao; Hirayama, Akiyoshi; Hitachi, Keisuke; Yamaguchi, Hisateru; Natsumeda, Manabu; Tateishi, Kensuke; Mukherjee, Joydeep; Pieper, Russell; Hirose, Yuichi
Abstract: IDH-wildtype and IDH-mutant glioma have different genetical and metabolic background although their histological appearances are similar. To reveal the difference in metabolites between IDH-wildtype and IDH-mutant glioma, two artificial cell lines made from normal human astrocyte, NHAE6E7hTERTRas (IDH-wildtype) and NHAE6E7hTERTIDHmut (IDH-mutant), were investigated. Capillary electrophoresis- and ion chromatography-coupled mass spectrometry revealed the lower amount of glutamine, glutamate and 2-oxoglutarate in NHAE6E7hTERTIDHmut cells than NHAE6E7hTERTRas cells. Pharmacological or genetical inhibition of GLUD1 which converts glutamate to 2-oxoglutarate, suppressed proliferation of the cells by inducing ROS and apoptosis in NHAE6E7hTERTIDHmut cells. ROS inhibitor, NAC suppressed GLUD1 inhibitor-induced ROS, apoptosis, and cytotoxicity in NHAE6E7hTERTIDHmut cells, revealing that cytotoxicity by GLUD1 inhibitor was at least partially due to the inhibitor-induced ROS. Exogeneous dimethyl 2-oxoglutarate rescued the cytotoxicity by GLUD1 inhibitor, suggesting decreased 2-oxoglutarate was associated with GLUD1 inhibitor-induced cytotoxicity. Mutant IDH1 overexpressed glioma cell line showed similar sensitivity to GLUD1 inhibitor to NHAE6E7hTERTIDHmut, which suggested that the difference of sensitivity to GLUD1 inhibitor was due to the status of mutant IDH. In conclusion, GLUD1 inhibitor will be new therapeutic options for IDH-mutant glioma.